2018
DOI: 10.17222/mit.2017.150
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of microstructures and oxidation behaviors of ytria and magnesia stabilized zirconia thermal barrier coatings (TBC)

Abstract: Thermal barrier coatings (TBCs) provide protection to minimize aggressive environmental conditions such as oxidation, corrosion and thermal shocks occurring at high temperatures. In this study, a CoNiCrAlY metallic-bond coat was deposited on an Inconel 718 superalloy substrate with a thickness about 100 μm using the atmospheric-plasma-spray (APS) method. The production of TBCs was accomplished by depositing Y2O3 partially stabilized zirconia (YSZ) and MgO-stabilized zirconia (MSZ) as two different ceramic top-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 26 publications
(41 reference statements)
0
6
0
3
Order By: Relevance
“…Kadir Mert Doleker et al was conducted porosity measurements of thermal barrier coatings. The results showed that that the thermal barrier coatings exhibit higher porosity 12 that improvement of brake thermal efficiency and reduction of SFC, CO, HC emissions 13 . In this investigation the piston is coated with CuCr1Zr to a thickness of 250 microns and it does not affect the compression ratio.…”
Section: Methodsmentioning
confidence: 99%
“…Kadir Mert Doleker et al was conducted porosity measurements of thermal barrier coatings. The results showed that that the thermal barrier coatings exhibit higher porosity 12 that improvement of brake thermal efficiency and reduction of SFC, CO, HC emissions 13 . In this investigation the piston is coated with CuCr1Zr to a thickness of 250 microns and it does not affect the compression ratio.…”
Section: Methodsmentioning
confidence: 99%
“…TGO yapı oluşum büyümesiyle öncelikle hacimsel genişleme ve sonrasında basma büyüme gerilmesi oluşabilmektedir. Oluşan ısıl genleşme uyumsuzluğu ve yüksek basma kalıntı gerilmesi de TGO yapısını olumsuz etkilemektedir [26]. Oluşan tüm bu durumlar neticesinde TBC sistemlerinde arayüzeyde ayrılma, kalkma ve pullanma gibi hasar oluşum mekanizmaları meydana gelebilmektedir.…”
Section: Materyal Ve Metod (Materials Andunclassified
“…Her iki TBC sisteminin termal özellikleri ile ilgili olarak, MSZ ve CSZ termal iletkenliği Y 2 O 3 +ZrO 2 (YSZ)' kinden nispeten daha düşüktür. Diğer yandan, MSZ ve CSZ sistemlerinin ısıl genleşme katsayısı YSZ kaplamaya yakın özellik göstermektedir [7]. Çok yüksek erime noktalarına sahip bu üst kaplama malzemeleri çoğunlukla termal sprey kaplama yöntemlerinden olan APS yöntemiyle üretilmektedir.…”
Section: Introductionunclassified
“…Kısmi olarak stabilitesi sağlanmış olan kaplamaların ani sıcaklık değişimlerinde faz kararlılığını koruyacağı ve faz değişiminden kaynaklanan hacim artışlarının önüne geçileceği düşünülmektedir. Kısmi stabilize zirkonya malzemesinin termal genleşmesinin saf zirkonyadan ve tamamen stabilize zirkonyadan daha düşük olması, tamamen stabilize ve monoklinik zirkonya fazından daha iyi bir termal şok direnci olduğu göstermektedir[7,17]. Üretilen MSZ ve CSZ TBC sistemlerine ait XRD analiz sonuçları…”
unclassified